WATER AND IDENTITY: AN ANALYSIS OF THE CAUVERY RIVER WATER DISPUTE - P.B. Anand (BCID Research Paper 3, 2004)
Abstract This paper focuses on the dispute over river Cauvery in Southern India. Among the causes of river water disputes are contested property rights, difficulty in enforcing such rights, conflict of uses and a lack of willingness to compromise. A co-operative outcome in such cases depends on several factors: asymmetry of power in a triadic relationship between a federal government and two riparian states (one upstream and one downstream). Other factors influencing co-operation are the extent to which the claims of river waters can be elevated from those of immediate riparian peoples to those of an entire state; the dominance of a masculine paradigm towards `taming' river waters using `hard' investments rather than `soft' and decentralised alternatives. On the basis of district level data, the importance of river Cauvery to the hydrology, economy and polity of the two contesting states is examined. This analysis helps us to appreciate why the two riparian state governments have limited room to manouvre. Drawing from two brief case studies of Murray Darling Basin and recent litigation in the USA, and other international experiences of river water treaties, the paper identifies various implications for the resolution of Cauvery and other river water disputes.